Balancing Digital Life And Family Harmony (A Critical Analysis Of Challenges And Solutions In Medan Maimun) - Yasir, Muhammad; Rubino, Rubino; Efendi, Erwan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to analyze the impact of gadget use on family harmony on the Deli River Bank, Kampung Baru, Medan Maimun District. The research method used is a qualitative approach with descriptive techniques. Data was collected through in-depth interviews and observations of mothers in the area during the period March to June 2024. This research found that gadget use varies among family members, with smartphones being the most dominant media. Gadgets are used for various purposes such as seeking information, entertainment and communication. Although gadgets increase productivity and access to information, excessive use can reduce the quality of interactions between family members and disrupt daily routines. Therefore, it is important for families to find a balance between gadget use and direct interaction to maintain harmony and emotional well-being.